2016
DOI: 10.1557/jmr.2015.400
|View full text |Cite
|
Sign up to set email alerts
|

Palladium seeded GaAs nanowires

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The substrate orientation also has a direct effect on the direction of grown NWs as observed from the results of the model. This phenomenon has also been observed earlier by several other research groups . Besides, with average droplet size of 180 nm we have achieved highest yield (77%) of vertical In x Ga 1−x As NWs on (100) surface reported in the literature …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The substrate orientation also has a direct effect on the direction of grown NWs as observed from the results of the model. This phenomenon has also been observed earlier by several other research groups . Besides, with average droplet size of 180 nm we have achieved highest yield (77%) of vertical In x Ga 1−x As NWs on (100) surface reported in the literature …”
Section: Resultssupporting
confidence: 89%
“…Researchers have also investigated the role of foreign nanoparticles other than Au for III–V NW growth. Growth of InP and GaAs NWs using Cu, Fe, Ni, Pd, Mn, and Sn has been investigated. However, very few studies are reported regarding the self‐seeded growth of In x Ga 1−x As NWs .…”
Section: Introductionmentioning
confidence: 99%
“…In the quest to achieve VLS in a non-self-catalyzed manner, Hallberg et al and Sun et al have performed pioneering work on alternative metals for the growth of III-arsenide and III-phosphide nanowires. For example, Pd-and Sn-catalyzed GaAs [128,129] and Cu-catalyzed InP [130,131] nanowire growth has recently been demonstrated. This area of research is still in its relatively early stages; high quality nanowires are still challenging to grow with catalyst metals other than Au.…”
Section: Catalyst Selectionmentioning
confidence: 99%
“…72,[74][75][76] As for [110] oriented ZB nanowires there can be several cross-section configurations from trapezoidal to diamond-like shapes and non-regular hexagons. 72,74,[77][78][79][80] WZ nanowires can be typically fabricated along [0001] with hexagonal cross-section, while WZ nanowires grown along [1120], and [1010] present square crosssection. 70,74,81 On the other hand, from a theoretical perspective nanowires are usually treated with cylindrical or square cross-section which simplifies the calculations without sacrificing the underlying physical features of the system.…”
Section: Nanowire Modelingmentioning
confidence: 99%